ISSUES OF APPLICATION OF MODERN MODELS IN THE DEVELOPMENT OF CLUSTERS IN THE REGION (Marketing Journal, 2025)
This article highlights the issues of applying modern models in the development of clusters in the region. In addition, scientific proposals and practical recommendations have been developed for the application of modern models in regional cluster developm ent.
Keywords: region; cluster; model; state; innovation cluster; agglomeration; regional development